Small is beautiful: evidence of an inverse relationship between farm size and yield in Turkey - Fatma Gül Ünal (Levy Economics Institute of Bard College, 2008)
This paper examines the relationship between farm size and yield per acre in Turkey using heretofore untapped data from a 2002 farm-level survey of 5,003 rural households. After controlling for village, household, and agroclimatic heterogeneity, a strong inverse relationship between farm size and yield is found to be prevalent in all regions of Turkey. The paper also investigates the impact of land fragmentation on productivity and labor input per acre, and finds a positive relationship. These results favor labor-centered theories that point to higher labor input per decare as the source of the inverse size-yield relationship.
Keywords: O12; Q12; 330; Farm size; productivity; allocative efficiency; Turkey